The Contribution of Organizational, Technological and Individual Factors on Information Systems Success in the Malaysian Public Sector - Hussein, Ramlah (2005)
Information System success has been widely discussed in the past two decades. As systems and technologies are being improved and developed, discussions on their effectiveness and evaluation on their success have been continuously debated by researchers, scholars and practitioners throughout the years. Consequently, factors affecting success of such systems are equally important. Based on the up-stream portion of the DeLone & McLean IS success model, the study investigates the antecedent factors and their combined effect on IS success.